Pengaruh Self Management Terhadap Risiko Komplikasi Pada Pasien Diabetes Mellitus Di RS Royal Prima Medan tahun 2024 - Saraswati, Nadya; Ananta Sellyta, Yismi; Dian Natalia Zega, Silvi; Basri, Basri (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Diabetes mellitus is a chronic metabolic disease characterized by elevated blood sugar (glucose) levels exceeding normal limits. The purpose of this study was to determine the effect of self-management on the risk of complications in diabetes mellitus patients at Royal Prima Hospital, Medan, in 2025. This quantitative study used a quasi-experimental design. The sampling technique used a total sampling of 35 patients. Data collection used an observation sheet. Data were analyzed using a Paired Samples Test. The results indicate that self-management has an effect on the risk of complications in diabetes mellitus patients. It is recommended that hospital management provide ongoing education to patients, their families, and patients regarding the importance of self-management.